Immune system stimulation by the gut symbiont Frischella perrara in the honey bee (Apis mellifera). Issue 9 (8th March 2017) - Emery, Olivier; Schmidt, Konstantin; Engel, Philipp
Abstract: Gut bacteria engage in various symbiotic interactions with their host and impact gut immunity and homeostasis in different ways. In honey bees, the gut microbiota is composed of a relatively simple, but highly specialized bacterial community. One of its members, the gammaproteobacterium Frischella perrara induces the so‐called scab phenotype, a dark‐coloured band that develops on the epithelial surface of the pylorus. To understand the underlying host response, we analysed transcriptome changes in the pylorus in response to bacterial colonization. We find that, in contrast to the gut bacterium Snodgrassella alvi, F. perrara causes strong activation of the host immune system. Besides pattern recognition receptors, antimicrobial peptides and transporter genes, the melanization cascade was upregulated by F. perrara, suggesting that the scab phenotype corresponds to a melanization response of the host. In addition, transcriptome analysis of hive bees with and without the scab phenotype showed that F. perrara also stimulates the immune system under in‐hive conditions in the presence of other gut bacterial species. Collectively, our study demonstrates that the presence of F. perrara influences gut immunity and homeostasis in the pylorus. This may have implications for bee health, because F. perrara prevalence differs between colonies and increased abundance of this bacterium has been shown to correlate with dietary alteration and impaired host development. Our transcriptome analysis sets the groundwork for investigating the interplay of bee gut symbionts with the host immune system.